Cloning and Expression of HA Gene from a Highly Pathogenic Avian Influenza Isolate (H5N1) in Thailand - Kriangkrai Witoonsatian; Theera Rukkwamsuk; Thaweesak Songserm; Theerapol Sirinarumitr (Agriculture and Natural Resources, 2007)
The avian influenza A virus hemagglutinin (HA) protein is encoded by viral gene segment IV and mediates early steps of the viral replication cycle, receptor binding and membrane fusion. This research was aimed to clone and express HA gene of avian influenza virus (AIV) in insect cell cultures using a baculovirus expression vector system. The viral RNA was extracted from the allantoic fluid of 9 to 11 days old chicken embryonic eggs. The extracted viral RNA was used as template for HA gene synthesis using RT-PCR 1,700 long. The amplicons were cloned into plasmid pFastBac HT and were transformed into E. coli strain DH10 Bac to produce the recombinant H5 baculovirus bacmids. The recombinant baculovirus DNA was further used to transfect and express in insect cell cultures. By SDSPAGE, the recombinant H5 protein was found to be 65 kDa in size. This protein was analyzed by dot blot and Western blotting using goat anti-H5 AIV polyclonal antibody and mouse anti-histidine monoclonal antibody. The results indicated that the HA gene was successfully cloned and the H5 protein could be expressed in insect cell cultures using a baculovirus expression vector system. Therefore, H5 protein could be further developed and applied as a candidate H5 AIV subunit vaccine.